-5(2x+7)=-3-6x

Simple and best practice solution for -5(2x+7)=-3-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2x+7)=-3-6x equation:


Simplifying
-5(2x + 7) = -3 + -6x

Reorder the terms:
-5(7 + 2x) = -3 + -6x
(7 * -5 + 2x * -5) = -3 + -6x
(-35 + -10x) = -3 + -6x

Solving
-35 + -10x = -3 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-35 + -10x + 6x = -3 + -6x + 6x

Combine like terms: -10x + 6x = -4x
-35 + -4x = -3 + -6x + 6x

Combine like terms: -6x + 6x = 0
-35 + -4x = -3 + 0
-35 + -4x = -3

Add '35' to each side of the equation.
-35 + 35 + -4x = -3 + 35

Combine like terms: -35 + 35 = 0
0 + -4x = -3 + 35
-4x = -3 + 35

Combine like terms: -3 + 35 = 32
-4x = 32

Divide each side by '-4'.
x = -8

Simplifying
x = -8

See similar equations:

| 4b+2(3b-8)=-25+7b | | 2x-1/6=3x-2/4 | | 5+9+4+6=0191 | | 4x^2-16y-7= | | 5(6+2x)=20 | | 8(x-2)+2=6x+2(-5+x) | | 7*a-2*5-2*6*a+5= | | x^2+7x+10=(x+5)(x+2) | | 5y-7=2y+11 | | 4+8+4+2=4396 | | 4+3+9+6=5482 | | .40x+.90(600)=.60(800+x) | | x^4+2x^3+3x^2+x+2=0 | | 6(2x-7)+6=12x-36 | | 39-5x=13x+19 | | -a^2+20a-60=0 | | 25x^2+10x+1=7 | | 16x^2-8x+1=11 | | x=4y*1.2 | | x^2-6x+9=9 | | 34=10+4q | | 5s^2+23s+24=0 | | -2X^2+14X+196=0 | | a+a=a | | 2q+2=-12 | | 4x^2+28X=240 | | 2x-4=x+9 | | (x-2)(3x+8)=0 | | ln(x)+ln(x-6)=ln(16) | | (50-4y)+(25-2x)=100 | | -36+2w=8w+w | | 7X-8X-9X+2+3+17X=12 |

Equations solver categories